The dream : Martin Luther King, Jr., and the speech that inspired a nation - Hansen, Drew D. (New York : Ecco, 2003)
A riveting account of the origins and legacy of "I Have a Dream" Forty years ago, Martin Luther King, Jr. electrified the nation when he delivered his "I Have a Dream" speech from the steps of the Lincoln Memorial. King's prophetic utterances started the long overdue process of changing America's idea of itself. His words would enter the American lexicon, galvanizing the civil rights movement, becoming a touchstone for all that the country might someday achieve. The Dream is the first book about Martin Luther King, Jr.'s legendary "I Have a Dream" speech. Opening with an enthralling account of the August day in 1963 that saw 250,000 Americans converge at the March on Washington, The Dream delves into the fascinating and little-known history of King's speech. Hansen explores King's compositional strategies and techniques, and proceeds to a brilliant analysis of the "I Have a Dream" speech itself, examining it on various levels: as a political treatise, a work of poetry, and as a masterfully delivered and improvised sermon bursting with biblical language and imagery. In tracing the legacy of "I Have a Dream" since 1963, The Dream insightfully considers how King's incomparable speech "has slowly remade the American imagination," and led us closer to King's visionary goal of a redeemed America.
Includes bibliographical references and index.
Keywords: King, Martin Luther, -- Jr., -- 1929-1968.; King, Martin Luther, -- Jr., -- 1929-1968 -- Oratory; Speeches, addresses, etc., American -- Washington (D.C.); March on Washington for Jobs and Freedom, Washington, D.C., 1963.; African Americans -- Civil rights -- History -- 20th century; Civil rights movements -- United States -- History -- 20th century; African Americans -- Biography; African American civil rights workers -- Biography; Baptists -- United States -- Clergy -- Biography; African Americans -- Biography